1981
DOI: 10.1139/x81-085
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of balsam fir and white spruce following a spruce budworm outbreak in the Ottawa River watershed in Quebec

Abstract: Spruce–fir stands in the Ottawa River watershed in Quebec were subjected to defoliation by spruce budworm, Choristoneurafumiferana (Clem.), between 1967 and 1975. Eighteen study plots were established in mixed and coniferous mature stands to determine impact of the infestation on balsam fir, Abiesbalsamea Mill., and white spruce, Piceaglauca (Moench) Voss, and the protracted mortality of these two species following the end of the infestation. The plots were established in 1975, the last year of defoliation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 0 publications
3
54
0
Order By: Relevance
“…The growth increase for birch and white-cedar at the OR site suggests that the outbreak at this location caused sufficient tree mortality and openings to favor the subsequent development of non-host species. This outbreak has been reported as a severe one [24], which could explain the persistence of the increased growth. Growth patterns for the PL site were more difficult to interpret for this period and did not show the same pattern.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The growth increase for birch and white-cedar at the OR site suggests that the outbreak at this location caused sufficient tree mortality and openings to favor the subsequent development of non-host species. This outbreak has been reported as a severe one [24], which could explain the persistence of the increased growth. Growth patterns for the PL site were more difficult to interpret for this period and did not show the same pattern.…”
Section: Discussionmentioning
confidence: 82%
“…According to Bouchard et al [22,25], who studied the region immediately north of our own, this outbreak was of a shorter duration and probably caused little mortality since stands remaining from the previous infestation were young and less vulnerable at that time. However, Blais [24], although providing no quantitative evidence, states that this outbreak may well have been quite severe within the study region. According to Morin [11], the growth decrease was not as marked compared with the other two outbreaks that occurred in the same century.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In New Brunswick, indications are that the 1870s spruce budworm outbreak was severe and stand-replacing (Etheridge et al 2005). Blais (1981) suggested that every second budworm outbreak caused higher mortality, because a standreplacing outbreak results in a less vulnerable younger stand for the succeeding outbreak. Long-term data on forest composition changes tend to be limited and localised.…”
Section: Are Anthropogenic Changes Amplifying Effects Of Outbreaking mentioning
confidence: 99%